Reading the Regions 2: Philippine Folk and Oral Traditions (NCCA 2021) - Supnet-Macansantos, Priscilla (LIRIP Journal of Interdisciplinary Studies; Vol 4 (2022): LIRIP Journal of Interdisciplinary Studies, 2023)
Book Review